Collaborative Governance dalam Pengelolaan Sampah di Kawasan Wisata (Studi Kasus pada Pantai Duta, Desa Randutatah, Kecamatan Paiton, Kabupaten Probolinggo) - Rahman, Siti Masfufah Salsabila; Hayat; Retno Wulan Sekarsari (Idarotuna : Journal of Administrative Science, 2025)
The purpose of this project is to implement the collaborative governance concept in trash management in the Probolinggo Regency's Duta Beach tourism region.  Issues with stakeholder collaboration and waste management are the driving force for this project.  Using a qualitative descriptive methodology, this study examines barriers and possibilities, plans and strategies to enhance cooperation from all stakeholders in waste management, pinpoints problems that occur, and develops solutions to maximize efficient and long-lasting cooperation.  According to the study's findings, Duta Beach is implementing the Collaborative Governance concept in a very effective manner. Improvements are still required, nevertheless, as a result of a number of issues that stakeholders must work together to tackle. Less structured waste management and issues with stakeholder participation are the primary causes of difficulties. However, by enhancing the government's role in creating legislation, boosting the capabilities of Pokdarwis (Tourism Awareness Groups), and teaching and interacting with local populations, there are chances to enhance cooperation. This study presents practical solutions for efficient and sustainable trash management through a collaborative approach, as well as theoretical contributions to the growth of the literature on collaborative governance in the context of garbage management in coastal tourist zones.